REGIONAL FACTORS IN THE FORMATION OF AGGLOMERATIONS - Ibragimov Ikboljon Ilxomjon ugli (Western European Studies, 2025)
The formation of agglomerations, which are concentrated areas of economic activity, is a multifaceted phenomenon, influenced by a large number of territorial factors. These factors include geographical, infrastructural and socio-economic dimensions, which together contribute to the emergence and sustainability of urban clusters. The importance of understanding these elements lies not only in their ability to shed light on the dynamics of urbanization, but also in their impact on regional planning and development. This article aims to examine the various territorial factors that contribute to the formation of agglomerations, focusing on examples from Asian and European contexts, in particular on the strategic location of infrastructure facilities.
Keywords: Agglomeration; urbanization; clusters